Business ethics and social responsibility in finance instruction: An abdication of responsibility - Hawley, Delvin D. (Journal of business ethics, 1991)
The shareholder wealth maximization objective for corporate management can be a very effective tool for decision making. However, it can also be used to rationalize the commission of unethical or socially irresponsible actions. Overemphasis on the SWM objective by some companies can lead to dangerous or disastrous consequences for consumers, employees, or the general population. Even so, issues of business ethics and social responsibility (BE-SR) are almost totally ignored in corporate finance textbooks. If the typical coverage of corporate finance courses is represented by these textbooks, then financial educators are abdicating their responsibility to help prepare future corporate managers to recognize and deal with BE-SR issues effectively.